PENGARUH PENGKOMPOSISIAN DAN PENYIMPANAN DINGIN TERHADAP PERUBAHAN KARAKTERISTIK SURIMI IKAN PARI (Trygon sp.) DAN IKAN KEMBUNG (Rastrelliger sp.) - Joko Santoso; Fie Ling; Ratna Handayani (Jurnal Akuatika, 2011)
High fat content in dark fleshed fish can affect on gel forming ability and high content of urea inelasmobranchii can arise ammonia odors in surimi product.Since surimi is an intermediate product, therefore storage of surimi in chill or frozen condition is usually performed. This experiment was carried out to study the effects of leaching, compositioning and chill storaging of stingray, mackerel and both combination surimi on the changes of physicochemical and microbiological properties. Three times leaching of minced-stingray could reduce the urea contents up to 95% and increased salt soluble protein (SSP) content 7.28%. Two times leaching of minced-mackerel could increase SSP content 8.24%. Surimi compositioning of stingray and mackerel in proportion 75%:25% gave the highest gel strength value 267.01 g cm. During 9 days chill storaging of surimi, the values of TVBN, and numbers of total microbes increased significantly. In opposite, the values of gel strength, WHC, whiteness, and SSP of surimi decreased continuously with the increasing time of chill storaging. Those indicated that physico-chemical and microbiologycal characteristics changes of surimi still occurred during 9 days of chill storaging.